O tolerancji politycznej z punktu widzenia Michaela Walzera - Dorota Sepczyńska (Analiza i Egzystencja, 2015)
The main focus of this article is little known in Poland political tolerance. The article aims to: reconstruct of Michael Walzer concept of the political tolerance; to place it in the typology of relativism – universalism; to make a first step towards the separation of political tolerance from personal tolerance for a general discussion of tolerance; demonstrate that tolerance is not only modern, liberal concept, associated with the individual freedom; show that the dispute about tolerance not only between the enemies.